Propranolol 0.2% Eye Micro-Drops for Retinopathy of Prematurity: A Prospective Phase IIB Study - Filippi, Luca; Cavallaro, Giacomo; Berti, Elettra; Padrini, Letizia; Araimo, Gabriella; Regiroli, Giulia; Raffaeli, Genny; Bozzetti, Valentina; Tagliabue, Paolo; Tomasini, Barbara; Mori, Annalisa; Buonocore, Giuseppe; et al. (Frontiers in Pediatrics, 2019)
Background: Oral propranolol reduces retinopathy of prematurity (ROP) progression, although not safely. Propranolol 0.1% eye micro-drops administered to newborns with stage 2 ROP are well-tolerated, but not sufficiently effective. Methods: A multi-center open-label trial was conducted to assess the safety and efficacy of propranolol 0.2% eye micro-drops in newborns with stage 1 ROP. The progression of the disease was evaluated with serial ophthalmologic examinations. Hemodynamic, respiratory, biochemical parameters, and propranolol plasma levels were monitored. Demographic and perinatal characteristics, co-morbidities and co-intervention incidences, together with ROP progression, were compared with a historical control group in the same centers participating in the trial. Results: Ninety-eight newborns were enrolled and compared with the historical control group. Populations were not perfectly homogeneous (as demonstrated by the differences in the Apgar score and the different incidence rate in surfactant administration and oxygen exposure). The progression to ROP stage 2 or 3 plus was significantly lower than the incidence expected on the basis of historical data (Risk Ratio 0.521, 95% CI 0.297– 0.916). No adverse effects related to propranolol were observed and the mean propranolol plasma level was significantly lower than the safety cut-off of 20 ng/mL. Unexpectedly, three newborns treated with oral propranolol before the appearance of ROP, showed a ROP that was unresponsive to propranolol eye micro-drops and required laser photocoagulation treatment. Conclusion: Propranolol 0.2% eye micro-drops were well-tolerated and appeared to reduce the ROP progression expected on the basis of a comparison with a historical control group. Propranolol administered too early appears to favor a more aggressive ROP, suggesting that a β-adrenoreceptor blockade is only useful during the proliferative phase. Further randomized placebo-controlled trials are required to confirm the current results. Clinical Trial Registration The trial was registered at ClinicalTrials.gov with Identifier NCT02504944 and with EudraCT Number 2014-005472-29.